Quality of life in patients with chronic slow-transit constipation according to the PAC-QOL questionnaire and the effectiveness of conservative therapy - Leshchyshyn, I. M.; Markulan, L. Y.; Okhotska, O. I.; Byk, P. L. (General Surgery, 2024)
Objective — to assess the quality of life (QOL) of patients with chronic slow‑transit constipation (CTC) according to the PAC‑QOL (Patient Assessment of Constipation Quality of Life) questionnaire, as well as the effectiveness of conservative therapy. Materials and methods. The study included 246 patients with chronic (more than 5 years) slow‑transit constipation (CSTC group) and 70 patients without CSTC (reference group). These individuals were examined and treated in the clinics of Bogomolets National Medical University from 2014 to 2023. The onset of chronic slow‑transit constipation often occurred at an average age of 22.2±0.8 years (from 1 year to 67 years) and lasted 20.2±0.7 years (from 5 to 53 years). The average duration of the delayed passage of stool was 9.4±0.3 days (from 3 to 22 days). All patients received an adjusted course of conservative treatment according to the Rome guidelines. The nosospecific PAC‑QOL questionnaire was used to evaluate the patients’ quality of life on their initial visit and 6—8 months after conservative therapy. Results. During the initial assessment, the CSTC group had a mean score of 3.03±0.56 on the «Physical Discomfort» subscale, while the reference group had a mean score of 1.19±0.29. On the «Psychosocial Discomfort» subscale, the CSTC group had a mean score of 2.21±0.52 compared to 0.84±0.18 in the reference group. The mean score for the «Worries and Concerns» subscale was 2.49±0.41 in the CSTC group and 0.77±0.24 in the reference group. The mean score for the «Satisfaction» subscale was 3.31±0.43 in the CSTC group and 0.86±0.28 in the reference group. The PAC‑QOL questionnaire total score was 2.63±0.26 in the CSTC group and 0.87±0.12 in the reference group (p <0.001 for all). After conservative treatment, the PAC‑QOL scores improved by an average of 40.4±20.0% (to 0.68—2.71 points). The cluster analysis revealed that after the course of conservative therapy, the PAC‑QOL questionnaire scores formed three distinct clusters: Cluster I — 0.68—1.39 points (49.2% of patients), Cluster II — 1.40—1.99 points (17.5% of patients), and Cluster III—2.0—2.8 points (33.3% of patients). These clusters represent good, satisfactory, and unsatisfactory results. Conclusions. The PAC‑QOL questionnaire revealed a statistically significant decline in QOL in patients with CSTC (2.63±0.26 points compared to 0.87±0.12 points in the reference group). Modern conservative treatment improved quality of life in 49.2% of cases. 17.5% of cases showed a satisfactory result, while the remaining ones exhibited insignificant or no improvement. Other treatment options, including surgery, should be considered for patients who do not respond to conservative therapy.